The effect of physical exercises in special (McHc) and (HcT) Describe the types of white blood cells to the players tennis - Ali Alkufi, Hussein (Journal of Physical Education, 2015)
In Pictures new information relating to training in a manner showing the need to conduct research that reveals images functional devices to the human body, which are affected by training in a manner so aim of this study was to investigate the effect of physical exercises in a variety in blood variables (McHc) and (HcT) and some blood cells (Almufosaat and Alentrovil and Monosaat) has been used as a researcher for the intentional sample and the number (6) players who represent elected Iraqi Army Sports Club Ground game of tennis, as well as use the curriculum Training to solve the problem of his research, has been used as a researcher also several tools and means tests was the most important use of physical exercise on the nature program, they were the duration of the program (eight) weeks, three training modules in the week, and time Section Chief in the module (35) minutes, and used In this method of training high intensity pulsation, and because of it, in order to get the desired results conducted before and after tests in the following variables were researcher reached several conclusions was the most important - is not affected by blood variables (McHc) and (HcT) Baltmarenat own and on the contrary, it kind of white blood cell values are significantly affected by the impact of the special exercises. The recommendations were the most important: - The use of other methods of training and testing of its impact on the research variables